DEVELOPMENT FACTORS OF THE REGIONAL TOURIST COMPLEX - DOLYNSKA, OLESIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article identifies factors that have a significant impact on the tourism and tourism complex development. It is determined that, the tourist complex is a typical intersectional complex, with a complex system of internal connections, based on the satisfaction of different people’s needs in the realization of tourist activities. It is mentioned that, the work of leading Ukrainian specialists in the geography of tourism points to the multifaceted nature and complexity of a clear and precise division of human activity into recreation and health improvement. This has led to different views on the factors of the development of the regional tourist complex. Traditionally, taking into account the theory of complex formation, they can be grouped into the following groups: economic, social, natural, ecological. The tourism territorial organization is one of the forms of economic processes social organization. It not only allows to indicate the most effective forms of spatial organization of economic processes, but also provides a scientific basis for the concept of sustainable development in understanding the optimization of economic processes and phenomena at the regional and local levels. The environmental impact of tourism is primarily related to such varieties as ecological and rural “green” tourism. They cannot exist only in the conditions of local natural landscapes preservation. The analysis of approaches to the selection of factors for the development of regional tourist complexes allows us to state that this remains a debatable issue in the geography of tourism. It is important to note that studying these factors we can raise the issue of territorial organization of regional tourist complex. For this purpose, it is necessary to define the available specialization of its territorial components and the complexity of the provision of tourism services. For the operation of tourism entities of various types, it is necessary to have a system of transport communications, water pipelines, gas and food pipelines, lines of communication and electricity, that is, a system of production infrastructure, without which no tourist complex is possible.
Keywords: tourist complex; recreation; factors of tourist activity development; sphere of services; accommodation establishments; cultural and historical monuments